The Relationship between Conflict Management Style and the Performance of HMJ PGMI UIN Sunan Gunung Djati Bandung Management - Tiarawati, Yara; Hidayat, Wahyu (Khalifah : Jurnal Pendidikan Nusantara, 2023)
Organizations consist of individuals who have different characters so that they can trigger a conflict that will interfere with the effectiveness of individuals in doing their jobs, therefore it is necessary to have a conflict management style that is used in dealing with conflict. This study aims to determine the correlation of conflict management styles (integration, willingness to help, dominating, avoiding, compromising) to the performance of the management of the department's student association. This research uses a quantitative approach with a descriptive-correlational design. The population of this study were all administrators of the student association majoring in PGMI UIN Sunan Gunung Djati Bandung with overall sampling of 48 people. Data collection techniques using a questionnaire. Research data analysis using descriptive analysis techniques Pearson Product Moment correlation. The results showed that there was a positive and significant correlation in the conflict management style of integration and willingness to help on the performance of the management board of the PGMI student association (HMJ) PGMI UIN Sunan Gunung Djati Bandung, for the conflict management style dominating and avoiding showed that there was no positive correlation to the performance of the management board of the student association, while the compromise conflict management style showed a positive but insignificant correlation.